Divindades indígenas numa ara inédita de Viseu (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper presents a new votive inscription discovered in recent archeological interventions in Viseu’s historical center. The monument is relevant to the paleo-hispanic studies and to the identification of Viseu’s ancient name.
Keywords: Chaerea; Deibabor / Deibobor; Vissaieigobor; *Vissaium; Viseu